The accretion history of the Universe with the SKA - Jarvis, M; Rawlings, S (2004)
In this paper we investigate how the Square Kilometre Array (SKA) can aid in determining the evolutionary history of active galactic nuclei (AGN) from redshifts z= 0 ->6. Given the vast collecting area of the SKA, it will be sensitive to both `radio-loud' AGN and the much more abundant `radio-quiet' AGN, namely the radio-quiet quasars and their `Type-II' counterparts, out to the highest redshifts. Not only will the SKA detect these sources but it will also often be able to measure their redshifts via the Hydrogen 21 cm line in emission and/or absorption. We construct a complete radio luminosity function (RLF) for AGN, combining the most recent determinations for powerful radio sources with an estimate of the RLF for radio-quiet objects using the hard X-ray luminosity function of Ueda et al., including both Type-I and Type-II AGN. We use this complete RLF to determine the optimal design of the SKA for investigating the accretion history of the Universe for which it is likely to be a uniquely powerful instrument.